Correction: Effects of sociodemographic and health factors on the self-management of non-communicable diseases among Chilean adults during the Covid-19 pandemic. - Daniela Nicoletti-Rojas; Rodrigo Retamal; Ricardo Cerda-Rioseco; Lorena Rodríguez-Osiac; Mauricio Fuentes-Alburquenque; Marcela Araya-Bannout (Public Library of Science (PLoS), 2023)
[This corrects the article DOI: 10.1371/journal.pgph.0000763.].